Literasi Keuangan, Gaya Hidup, dan Pengelolaan Keuangan Mahasiswa Akuntansi: Pembelajaran Akuntansi Keuangan sebagai Variabel Moderasi - Suyanto, Suyanto; Putri, Fuadhillah Kirana; Dewi, Wahyu Prastika (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2024)
The gap between the financial literacy index and financial inclusion in society is what has triggered the emergence of the problem of illegal online loans among students. The rise in loan cases occurs as a result of poor financial management and high levels of consumption. The aim of this research is to examine the influence of financial literacy and lifestyle variables on student financial management with financial accounting learning as a moderating variable. The data used is primary data obtained from distributing questionnaires using Google Form. Data was measured using a Linkert scale with the research population, namely accounting students throughout Indonesia. The sampling technique uses purposive sampling. This research obtained a sample of 203 respondents. The regression method is used as a data analysis method which is processed using IBM SPSS 23. The research results show that financial literacy has a positive effect on student financial management. Lifestyle has a positive influence on student financial management. Learning financial accounting strengthens the influence of financial literacy on students’ financial management. Learning financial accounting weakens the relationship between the influence of lifestyle on students’ financial management.